Automated double glazing convex lens skylight / Nurul Anis Izzati Khairul Aizam and Nor Azizah Talkis - Khairul Aizam, Nurul Anis Izzati; Talkis, Nor Azizah (2023)
Skylights can pose various issues such as excessive glare, heat gain, discomfort, leaks which may lead to property damage, and increased repair expenses. Hence, proper installation, careful consideration of size and type, regular maintenance, and selection of suitable skylight design are all essential factors for users to avoid any issues and maximise the benefits of having a skylight particularly for terrace house with pitch roof. Therefore, this research is aimed at developing an innovation of skylight to overcome the issues related to the existing skylights. To achieve the aim, four objectives have been established which are to develop an enhanced skylight design ideas, i.e., Automated Double Glazing Convex Lens Skylight, assemble the proposed design, demonstrate its performance, and demonstrate its marketability potential particularly for residential buildings. The methods used in this study are the collection of primary and secondary data in order to achieve the objectives. The innovation idea was derived from several reviews of the existing skylights to overcome the identified issues.